PENGARUH PEMBELAJARAN FUTSAL TERHADAP FUNGSI ATENSI DAN MEMORI KOGNITIF SISWA - Melsaz Nur Al aziz, - (2017)
The purpose of this research are to determine the effect of lerning football (futsal) game to improved cognitive function of attention and memory function of students. The method used in this research is experiment research. The sample used in this research is 20 students from class VIII A, VIII B, VIIII C out of 157 students from class VII in SMPN 1 Bojongsoang. The research design used in this research is one group pretest-posttest design. The instruments used are Grid Concentration Exercise, Digit Memory Test, and Academic Potential Test (TPA). The data analysis used in this research is the T test. The result of this research shows thattcount 5,50 is bigger than ttable 2,086. This means that futsal learning has an effect on attenuation function and students' cognitive memory significantly. The suggestion related to this research is that further research on cognitive function need to be conducted by involving more samples and with other variables.---- Tujuan penelitian ini untuk mengetahui s pengaruh pembelajaran permainan futsal terhdap peningkatan fungsi kognitif atensi dan fungsi memori siswa. Metode yang digunakan adalah eksperimen. Sampel yang digunakan adalah 20 siswa terdiri dari kelas VIII A, VIII B, VIIII C dari 157 siswa kelas VII di SMPN 1 Bojongsoang. Desain penelelitian adalah 0ne group pretest posstest design.Instrumen yang digunakan yaitu Grid Concentration Exercise, Digit Memory Test, dan Tes Potensi Akademik (TPA). Analisis data menggunakan uji t. Hasil penelitian diperoleh bahwa thitung 5,50 lebih besar darittabel 2,086. Yang artinya pembelajaran futsal berpengaruh s ecara signifikan terhadap fungsi atensi dan memori kognitif siswa s . Saran terkait penelitian ini Perlu diadakan penelitian lebih lanjut mengenai fungsi kognitif dengan melibatkan lebih banyak sampel dan dengan variabel yang lain.